The relationship between shipping freight rates and inflation in the Euro Area - Michail, Nektarios A.; Melas, Konstantinos D.; Cleanthous, Lena (My University, 2022)
Consumer inflation across the globe has rebounded during 2021 due to supply-side disruptions, one of which is the increase in freight costs. To elaborate on the relationship between inflation and shipping costs, we employ a Vector Error Correction Model (VECM) and use disaggregated monthly data from January 2009 to August 2021, using both constant tax and the standard price indices. Following a shock in freight rates, the most hard-hit sectors appear to be garments and major household appliances, items that have traditionally been manufactured outside the euro area. In addition, using a threshold regression methodology, we show that when freight rates rise more than $1300-$1500 per day, the sensitivity of inflation to freight changes increases.
Keywords: Inflation; Shipping; Freight rates; Supply shock